1996
DOI: 10.1366/0003702963905501
|View full text |Cite
|
Sign up to set email alerts
|

Raman Investigation of Photopolymerization Reactions of Single Optically Levitated Microparticles

Abstract: Raman spectroscopy was used to investigate polymerization reactions in a single micrometer-sized monomer droplet. An Ar+ laser levitated the microparticles and simultaneously excited the Raman scattering. The polymerization reaction was initiated by exposing the monomer droplets to the UV radiation of a mercury arc excitation lamp. The Raman spectrum of the reacting particle was investigated on-line. The results demonstrate that the combination of the technique of optical levitation and Raman spectroscopy allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 19 publications
1
38
0
1
Order By: Relevance
“…Similar experiments were performed by Esen et al who used UV light from a mercury arc lamp to initiate the polymerization in the trapped acrylate aerosol droplet [411]. The dynamics of cooling and evaporation of a single levitated sulfuric acid/H 2 O droplet exposed to surrounding gaseous atmosphere of varying humidity was studied by Mund and Zellner [412].…”
Section: Raman Spectroscopy Of Optically Trapped Objects: Raman Tweezersmentioning
confidence: 72%
See 1 more Smart Citation
“…Similar experiments were performed by Esen et al who used UV light from a mercury arc lamp to initiate the polymerization in the trapped acrylate aerosol droplet [411]. The dynamics of cooling and evaporation of a single levitated sulfuric acid/H 2 O droplet exposed to surrounding gaseous atmosphere of varying humidity was studied by Mund and Zellner [412].…”
Section: Raman Spectroscopy Of Optically Trapped Objects: Raman Tweezersmentioning
confidence: 72%
“…Raman -see Section 4.8) are especially attractive for studying the properties of aerosols as they enable to isolate an individual aerosol particle and study its composition and dynamics [58,408,412,413,471]. To this end, single-beam, dual-beam, and HOT have been used to manipulate with aerosols, perform controlled coagulation of selected aerosol particles [472], or enhance their Raman scattering signal and study the evolution of the droplet size by employing size-and refractive-indexdependent structural Mie resonances in the droplets [410,411,473].…”
Section: Micro-manipulation Of Aerosolsmentioning
confidence: 99%
“…They are assigned to the aromatic ring vibration of the photoinitiator, the monomers carbon–carbon double bond stretching, and the monomers carbonyl group stretching, respectively. 36 Since the concentration of carbon–carbon double bonds diminishes during polymerization, the peak intensity at 1635 cm −1 becomes smaller as a consequence. The other two peaks should stay unaltered based on the fact that neither the aromatic ring of the photoinitiator nor the carbonyl group of the monomers participates in the polymerization reaction.…”
Section: Resultsmentioning
confidence: 99%
“…When coupled with micro‐Raman scattering, the composition, size and phase partitioning of different chemical components within a liquid or solid droplet can be investigated, and then, many fundamental physical and chemical processes at the single particle scale with in situ conditions have been unravelled . Although photochemical processes are of prime importance in physical chemistry, the single particle studies were mainly dedicated to the photopolymerization of single optically levitated particles . Authors demonstrated the reaction in a single micrometer‐sized monomer droplet initiated by UV radiation.…”
Section: Introductionmentioning
confidence: 99%